2010
DOI: 10.1021/es102837p
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Isotopes (129I and 127I) in the Baltic Proper, Kattegat, and Skagerrak Basins

Abstract: Radioactive anthropogenic pollution has raised concerns about the present and future environmental status of the semienclosed Baltic Sea. We here study the distribution and inventory of the anthropogenic radioactive (129)I in water depth profiles collected from 16 sites in August 2006 and 19 sites in April 2007 in the Baltic Proper and related Kattegat and Skagerrak basins. The results reveal considerable differences of (129)I concentration in terms of spatial and temporal variability and expose relatively hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In the North Sea, Baltic Sea, Norwegian Sea and Arctic, 129 I/ 127 I ratios of 10 −8 –10 −6 were reported because of huge amount of 129 I discharged from the European nuclear fuel reprocessing plants (NFRPs)at Sellafield (UK) and La Hague (France) has dispersed with sea current to these area417181920. In the Fukushima offshore water, the 129 I/ 127 I ratios reached to 2.2 × 10 −9 (6.3 × 10 8  atoms/L for 129 I concentration) due to the releases from the Fukushima accident10 (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…In the North Sea, Baltic Sea, Norwegian Sea and Arctic, 129 I/ 127 I ratios of 10 −8 –10 −6 were reported because of huge amount of 129 I discharged from the European nuclear fuel reprocessing plants (NFRPs)at Sellafield (UK) and La Hague (France) has dispersed with sea current to these area417181920. In the Fukushima offshore water, the 129 I/ 127 I ratios reached to 2.2 × 10 −9 (6.3 × 10 8  atoms/L for 129 I concentration) due to the releases from the Fukushima accident10 (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, to reduce the chances of the physical uptake of rarer radioactive isotopes from the environment, 127 I can be used in large doses. Nevertheless, studies reveal 6,7 that this approach is dangerous in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Data on total iodine isotopes ( 127 I and 129 I) and their species ( 127 I − , 129 I − , 127 IO 3 − , and 129 IO 3 − ) in surface water (above 10 m depth) of the regions studied here were published by Yi et al 18 and Hansen et al, 19 respectively. Iodine analyses of depth profiles presented here (Table S1 of Iodine Isotopes Variability with Depth.…”
Section: ■ Resultsmentioning
confidence: 99%
“…9 Furthermore some studies have shown that iodide may be supplied to the water body through organic matter decay and diagenetic release from sediment by diffusion process. 18,30,31 For abiotic reduction process, reducing agents such as iron and manganese can promote the removal of oxygen from iodate and the reduction into iodide in anoxic environment. 32 The reduction may happen in deep or surface water depending on environmental conditions and several reactions have been proposed for the iodate reduction process including:…”
Section: ■ Resultsmentioning
confidence: 99%